Integrated Management of Diseases Caused by Fungi, Phytoplasma and Bacteria - Ciancio, Aurelio; Mukerji, K.G (Integrated Management of Plant Pests and Diseases, 2008)
The third volume of the series covers, in three Sections, emerging issues in the integrated management of main diseases of perennial and annual crops. The chapters provide basic data about the diseases concerned, in order to facilitate their detection and recognition either by field and laboratory inspection, discussing the main management possibilities experienced by farmers, plant pathologists and consultants, in different areas of the world. The first Section covers key diseases of stone fruit and apple trees, as well as the phytoplasma diseases of grapevine and fruit crops, the citrus diseases caused by Phytophthora spp., and the management of chestnut diseases, esca complex on grapevine and Rosellinia necatrix root rot. In the second Section, on annual crops, a first chapter describes the use of simulation models for potato late blight management, followed by a review about the potentials of the decision support systems approach, with an example of integrated forecasting system for Phytophthora infestans on potato. Following chapters review the management of bacterial fruit-blotch on cucurbits, Verticillium wilt on tomato, Sclerotinia rot on carrot, and cotton and rice diseases. A further review describes biological and integrated means to control rust diseases. In the third, final Section, two innovating approaches to disease management are reviewed: DNA fingerprinting methods, for microbial pathogens diagnostics with potentials in taxonomy and plant protection, and the management of pests and diseases through the exploitation of endophytes and their metabolites, a new research field with interesting perspectives and benefits in IPM/IDM.